CV-159, a Unique Dihydropyridine Derivative, Prevents TNF-Induced Inflammatory Responses in Human Umbilical Vein Endothelial Cells - Tatsuya Usui; Hideyuki Yamawaki; Masato Kamibayashi; Muneyoshi Okada; Yukio Hara (Elsevier, 2010)
CV-159, a 1,4-dihydropyridine derivative, has Ca2+antagonistic and anti-calmodulin actions. An early feature of atherosclerosis is vascular endothelial inflammatory change. We examined whether CV-159 has protective effects against endothelial inflammatory responses. After pretreatment of human umbilical vein endothelial cells (ECs) with CV-159 (10 μM, 30 min), TNF-α (10 ng/ml) was applied for 20 min or 24 h. Expressions of inflammatory markers and activation of inflammatory signal molecules were examined by Western blotting. Reactive oxygen species (ROS) generation was examined by using 2',7'-dichlorodihydrofluorescein diacetate. CV-159 inhibited TNF (24 h)-induced expression of e-selectin but not vascular cell adhesion molecule-1 and intercellular adhesion molecule-1. CV-159 inhibited TNF (20 min)-induced phosphorylation of JNK, p38, and NF-κ B p65 (Ser536). A JNK inhibitor, SP600125, and a p38 inhibitor, SB203580, inhibited TNF-induced e-selectin expression. An antioxidant drug, N-acetyl-l-cysteine (NAC), inhibited TNF-induced e-selectin expression. NAC inhibited TNF-induced phosphorylation of JNK and p38 but not NF-κB. CV-159 inhibited TNF-induced ROS generation. Our results indicate that in ECs CV-159 specifically inhibits TNF-induced e-selectin expression through inhibition of JNK, p38, and NF-κB phosphorylation. It is suggested that CV-159 prevents activation of JNK and p38 through inhibition of ROS, while it prevents activation of NF-κB via a ROS-independent manner. Keywords:: dihydropyridine derivative, vascular endothelium, inflammation, signal transduction, reactive oxygen species